2021
DOI: 10.1111/ene.14907
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of outcome measures in chronic inflammatory demyelinating polyneuropathy: A study of the Inflammatory Rasch‐built Overall Disability Scale

Abstract: The use of objective outcome measures in chronic inflammatory demyelinating polyneuropathy (CIDP) is recommended by international guidelines [1] and has become more widespread in recent years [2]. Different outcome measures are in use and despite debate about their validity in different populations or disease subtype, they are generally currently widely accepted and used as the best available means of evaluating treatment effects and monitoring disability in subjects with CIDP [2]. Patient-reported outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The considerable variability in outcome measures on visits without meaningful deterioration according to the treatment or patient anchor we observed may be explained by various factors, including minor (treatment related) symptom fluctuations, changes in mood, pain or fatigue and inconsistencies due to misunderstanding of the items or answer categories of questionnaire, poor interrater reliability for the MRC‐SS, or suboptimal method of measurement such when assessing grip strength 10,12,16,23‐25 . In addition, specifically applicable for our study, variability may be also influenced by blinding of patients and potential nocebo effects 15 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The considerable variability in outcome measures on visits without meaningful deterioration according to the treatment or patient anchor we observed may be explained by various factors, including minor (treatment related) symptom fluctuations, changes in mood, pain or fatigue and inconsistencies due to misunderstanding of the items or answer categories of questionnaire, poor interrater reliability for the MRC‐SS, or suboptimal method of measurement such when assessing grip strength 10,12,16,23‐25 . In addition, specifically applicable for our study, variability may be also influenced by blinding of patients and potential nocebo effects 15 .…”
Section: Discussionmentioning
confidence: 89%
“…assessing grip strength. 10,12,16,[23][24][25] In addition, specifically applicable for our study, variability may be also influenced by blinding of patients and potential nocebo effects. 15 Recently, a retrospective study that included stable, IgG-treated CIDP patients found that, during routine care, the MCIDs of the 4 centiles of I-RODS, 8 kg of grip strength (using a Jamar dynamometer) and 2 points on the MRC-SS were met in 44%, 11% and 44%, respectively.…”
Section: Visits With Deteriorationmentioning
confidence: 99%
“…In the PRIMA study, 13 18 The CIDP population studied was heterogeneous in relation to disease duration and subtype and further subanalyses were not possible. Furthermore, these would have been limited by small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…For strength measures (MRCSS and grip), it is possible that, after early plateauing, further but slower improvement, particularly of proprioceptive function, allowed subsequent functional improvement, as measured on the adjusted INCAT. The early plateauing of the I‐RODS score may relate to possible inadequacy of a standard MID cut‐off of 4 points, irrespective of baseline, or to issues directly related to the scale's validity in the setting of the heterogeneity of CIDP 18 . The CIDP population studied was heterogeneous in relation to disease duration and subtype and further subanalyses were not possible.…”
Section: Discussionmentioning
confidence: 99%
“…MUNIX, EDx, clinical outcome measures, including MRCSS, ONLS, R-ODS, Jamar handgrip dynamometry, timed 10-meter walk test (10MWT), pinch power test, and nine-hole peg test (NHPT), were performed at baseline and after 6 months, according to previously validated and published protocols. [17][18][19] Manual muscle testing was used to measure the muscle strength bilaterally according to the MRCSS (ranging from 0 to 60 points) for shoulder abduction, elbow flexion, wrist extension in upper extremities and hip flexion, knee extension, and ankle dorsiflexion in the lower extremities.…”
Section: Functional Measuresmentioning
confidence: 99%